Need of Soft Skills for Undergraduate Urban Youth for Career Development - Gautam, Suresh (Journal of Training and Development, 2016)
The paper aims to show the importance of soft skills of the undergraduate urban youth who are preparing their career within Nepal or abroad. Youth in city pursue formal education from colleges and university in Nepal. After the completion of undergraduates, they prepare themselves for the job market. In this line, I argue that those youth who have not developed their soft skills struggle much to find out a job. It also increases the urban poverty and unemployment. I employed ethnographic research approach to explore everyday life activities of urban youth showing their preparedness of career. In doing so, I am telling credible, rigorous, and authentic stories of those undergraduate urban youth who are preparing their career in Kathmandu. The research is carried out in Kathmandu with four young research participants who are going to appear their final semester examination of undergraduate level in Management stream from a private college of Kathmandu. Two of them have just started working in companies and two of them are searching jobs. Applying the soft skill perspective the paper explores the situation of undergraduate youth in Kathmandu who theoretically learned about some soft skills in colleges and university during their academic hours but they hardly practiced in working environment. The research explores that it is not enough to deliver theories of soft skills in the classroom rather practice for youth who are going to start their career in the city.